ГОСПОЖА ПРОФЕССОР РОЗА АЛИМПИЕВА В ОЛЬШТЫНСКИХ ПУБЛИКАЦИЯХ - Rudziewicz, Irena (Acta Neophilologica, 2019)
Professor at Immanuel Kant Baltic Federal University, a Slavist, a scholar dealing with comparative linguistics and the semantics of Slavic languages, the author of many scientific publications, including studies, monographs, books and various articles.